Presidential discretion - Chatterjee, Debtoru (New Delhi : Oxford University Press, 2016)
This title examines the discretionary powers of the President of India. It is replete with examples mainly drawn from India, the Commonwealth countries, and Great Britain, of actual instances of exercise of such powers by a constitutional sovereign. For instance, the book flags the crucial role a President can play in the event of a hung parliament.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 22, 2016).
Keywords: Executive power -- India; Presidents -- India; India -- Politics and government; Sovereignty; Politics and Government; Public administration